ANALISIS DIREKTORI PERPUSTAKAAN PERGURUAN TINGGI KRISTEN DI INDONESIA TAHUN 2012 - Nani Rahayu, Rochani (BACA: Jurnal Dokumentasi dan Informasi, 2013)
This study aims to determine: 1) the number of Indonesian Christian University Library based on provinces; 2) the number of collections based on titles and copies; 3) the number of digital collections; 4) the amount of budget provided; 5) the number of librarians in the library unit. The study used descriptive method. Data were obtained from Christian Library University Directory in Indonesia published by Petra Christian University in 2012 with ISBN 978-602-18143-07. There are 59 libraries listed. Analyzing data used Microsoft Excel 2007 and the result presented in the form of tables and figures. The study result are as follows: 1) East Java was the first rank province with 12 libraries (20,33%), DKI was in the second rank and had 10 libraries ( 16,95%). The third rank was West and Central Java with 7 libraries (11,86%); 2) The first rank for library size was West Java with 6.765 m2 (24,74%), Banten province was in the second place with 5.000 m2 (18,28%), and the third was East Java with 4.801 m2 (17, 56 %). 3) It is found that East Java is the most have number of collections with a total of 153.600 titles and secondly was DKI with a total of 91.312 titles and thirdly was Banten Province (71.529 titles or 2,47%). East Java was the first rank in the digital collection i.e.114.346 titles (67,52%), DKI in the second position with a total of 14.724 titles (14,59%) and in the third place was Central Java (15.292 titles or 9,02%); 4) Central Java had a total of 85 librarians (15,52%) in the first rank, the second rank was DKI with a total of 69 librarians (20,72%) and the third position was 53 librarians (15,91%); 5) DKI provided Rp. 848.251.247 (32,95%) in the first rank, while in the second rank was Banten province i.e. Rp. 600.000.000 (23,30%) and in the third rank was Eat Java (Rp. 461.408.050 or 17,92%). The conclusions were: 1) Each province in Indonesia has Christian University Library; 2) Each library has librarian, except in West Kalimantan Province; 3) West Kalimantan, South Kalimantan, East Kalimantan, Maluku, East Nusa Tenggara, Central Sulawesi and North Sulawesi do not have digital collection and they do not have some budget for purchasing collections in 2012.